Vehicle Recovery Services and Road Safety Compliance in Port Harcourt Metropolis - Budnukaeku, Alexander Chinago; Babajide, Fanoiki Solomon (Law and Economy, 2025)
This study investigates vehicle recovery services and road safety compliance in the Port Harcourt metropolis. In order to evaluate the state of vehicle recovery services and road safety compliance in the city, a questionnaire was prepared to assess vehicle recovery services and road safety compliance based on 4 main categories: Impact, availability and affordability, performance and challenges. The statistical analysis and tools employed were simple percentage (%) tables and charts. The findings obtained revealed that there are areas for improvement with regard to vehicle recovery in the city, particularly with respect to breakdowns. Distressed vehicles which for one reason or the other are not recovered quickly, contribute significantly to hindering smooth traffic flow, could contribute to secondary crashes and in themselves, contribute to a reduction in road safety compliance. The study recommended that the Rivers State Ministry of Transport should be involved in regulating vehicle recovery services in the state and shaping policy that affects the sector. The involvement of the Ministry in increasing driver education will also contribute towards improving road safety compliance in the state.